PERTUMBUHAN DAN HASIL TIGA VARIETAS PADI GOGO PADA PERLAKUAN PEMUPUKAN - Laila Nazirah; B. Sengli J. Damanik (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
An effort to anticipate a food crisis is to increase food production by planting upland rice in dry lands. In addition, provision of appropriate fertilizer has great potential for strengthening food self-sufficiency and for future agricultural development. The study was aimed at determining growth and yield of three varieties of upland rice under a compound fertilizer. The experiment was arranged in split plot design, consisting of three upland rice varieties and three levels of compound fertilizer. The main plot was upland rice varieties, i.e. Inpago 4, Inpago 5, and Inpago 8, while the subplot was compound fertilizer, i.e. a dose of 0 kg/ha, 150 kg/ha, and 250 kg/ha. Results showed that varieties significantly affected plant height, panicle numbers, and panicle length, but did not significant affect weight of 1000 grains and dried grain. Inpago 4 was the best variety. The best of NPK fertilizer was found at dose of 250 kg/ha.